Analysis of the use of digital technologies in the tourism sector: Evidence from Kazakhstan - Ramazanova, Makhabbat (2022)
In contemporary times, digital technologies are recognized as a vital tool in socio-economic development in many countries, as well as their prerequisite is recognized for many industries, including tourism. The growth of information and communication technologies, demand for digitalization in various economic sectors, challenges many destinations towards the introduction and development of digital technologies in the tourism sector. In this context, the objective of the present book chapter is to explore the current state of the digital technology application in the tourism industry and identify the limitations and problems associated with their implementation in the case of Kazakhstan, as an emerging and promising tourism destination. Using the gravity model, we examine the impact of information and communication technology on the tourism demand of Kazakhstan for the period of 2000–2018. The secondary data has been compiled and decomposed from international organizations, the ministries, national and regional authorities of Kazakhstan. The study updates traditional policy implications and provides remarkable recommendations for applications of digital technologies in the tourism development of the country.